Comparative wood anatomy and computerised identification of dryobalanops species in Sarawak - Andrew, Tukau Salang (Universiti Malaysia Sarawak (UNIMAS), 2003)
All species showed that there were variations in the anatomical characteristics across Inmk (within tree). between trees and species. Within tree, there were also distinct in the anatomical characteristics between the juvenile wood and matured wood. The juvenile wood was around the pith up to a relative distance of 0.4 from the pith and the wood was beyond the relative distance of 0.4 until the sapwood. The matured wood the true characteristics of the timber. Variations between trees were suspected to to differences in sites while between species were due to both genetic and sites differences.